Introduction Blended Learning Designs on Introduction to Linguistics at West Indonesian - ., Yendra; Satria, Willy; Rahmat, Wahyudi; Kemal, Edwar; Kusumaningsih, Dewi; Sudiyana, Benedictus; Miji Lestari, Prembayun; Susanti, Ratna; Agung Ayu Dian Andriyani, Anak; Susylowati, Eka; Budi Santoso, Agus; Bambang Putut Setiyadi, Dwi; et al. (International Journal of Engineering and Technology, 2018)
Learning methods that used to be done only face-to-face in the classroom and make the educator as a center of information (conventional) gradually begin to change towards learning that is also on-line based on the internet as an information center (E-Learning internet based). In STKIP PGRI Sumatera Barat E-Learning internet based learning method itself has been introduced and implemented since 2014, but has not been maximally optimized. This is because the method does not have a standard in its implementation, and also conventional face-to-face learning method cannot be abandoned completely, hence there is overlap between the two. Accordingly, this study developed a model of learning that combines the concept of conventional learning with the concept of E-Learning internet based called Blended Learning. Blended Learning model is expected to be a solution to the above problems, so that the learning process can be implemented effectively. This research outcome is a product that is learning model design. Â